Plan de negocios para la creación de una empresa productora de dulces nutritivos “KANDY JAS”. - Jarrin Pilataxi, Ruth Stefany (2024)
The increase in unhealthy food products, especially aimed at children, has raised concerns as it is associated with the increase in chronic diseases. In Ecuador, 23% of children under five years of age suffer from chronic malnutrition, while 35% of children between 5 and 11 years old are overweight or obese, according to the National Health and Nutrition Survey (ENSANUT). Aware of the importance of instilling healthy habits from childhood, the KandyJas business initiative emerged, focused on the production of healthy jellies with natural ingredients such as lemon and ginger, providing important benefits to the consumer's health. This project seeks to evaluate the viability of KandyJas through a business plan that includes a market study with 4,593 children and young people from 5 to 14 years old, achieving an acceptance of 90% in a sample of 355 participants. Considering field information, the availability of raw materials and human talent, the project will have a used capacity of 107,777 gelatins per year. The marketing strategy that the company will implement will be based on the marketing mix, addressing aspects such as product, price, place and promotion. In financial terms, the indicators reveal a NPV of $46,664.78 and an IRR of 25%, consolidating the viability and feasibility of the project.